The Effect of Cross-Modal Sensory Integration on Elementary Students' Retention and Motivation in Integrated Science-Social Studies Learning - Dhebi Ariska; Lilik Sri Hariani; Rusno Rusno (Abjadia : International Journal of Education, 2026)
This study aims to analyze the influence of multisensory integration through the Cross-Modal Sensory Integration model on the retention and learning motivation of elementary school students. The study uses a quantitative approach with a quasi-experimental type and a non-equivalent control group design. The study subjects consisted of 54 elementary school grade V students who were divided into experimental groups and control groups. The experimental group obtained IPAS learning using the Cross-Modal Sensory Integration model, while the control group used conventional learning. Data were collected through learning retention tests and learning motivation questionnaires, then analyzed using descriptive statistics and independent sample t-test. The results showed that there was a significant difference between the experimental group and the control group in the retention and motivation variables of learning with a significance value of p 0.05. Students who participated in learning with the Cross-Modal Sensory Integration model had higher long-term retention abilities and learning motivation than students who participated in conventional learning. These findings show that multisensory integration through the Cross-Modal Sensory Integration model is effectively applied in social studies learning to improve the quality of the learning process and outcomes of elementary school students.